The effect of use educational curriculum designer by Random Excitement Strategies In breaststroke technical performance learning - م.د بثينة عبد الخالق أ.م.رشوان محمد الهاشم (الرياضة المعاصرة)
Swimming is one of the entertaining sports which is highly emphasized by the     developed countries, it can be practiced by any age group as it is an exciting sport.